(untitled) (Impetus, 2021)
This article explores the tension in the existing relationships of power in the sport, specifically in archery in Colombia, by the identification of those entities involved that through this sport are important for the nation, as well as the value of the body in archery. In relation to the body and corporeality, even though archery has ceased to be an elitist sport as a consequence of the current sport system, it remains as a space in which sexism, racism and classism dynamics are present. So it is required a process of transformation into a space of respect and social equality. Other dynamics where discrimination is also present are those related to age, which are founded on the belief that the younger the more capabilities, or those related to sportsmen/women who are not in the high performance level but rather practice the sport for recreation. These are the “bodies that do not matter”.